2010
DOI: 10.1016/j.biochi.2010.04.026
|View full text |Cite
|
Sign up to set email alerts
|

Metallo-aminopeptidase inhibitors

Abstract: Aminopeptidases are enzymes that selectively hydrolyze an amino acid residue from the N-terminus of proteins and peptides. They are important for the proper functioning of prokaryotic and eukaryotic cells, but very often are central players in the devastating human diseases like cancer, malaria and diabetes. The largest aminopeptidase group include enzymes containing metal ion(s) in their active centers, which often determines the type of inhibitors that are the most suitable for them. Effective ligands mostly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
101
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 119 publications
(103 citation statements)
references
References 197 publications
1
101
1
Order By: Relevance
“…APN is a zinc-binding type 2 transmembrane ectopeptidase of 150 kDa (Clan MA, family M1; Merops, the peptidase database) that is expressed selectively in vascular endothelial cells, including HUVECs and aortic endothelial cells (32). Previously, it has been shown that a synthetic NGR-containing peptide derived from endostatin (corresponding to the Ser-1451-Thr-1464 moiety and encompassing the sequence of presently identified peptides) binds to and inhibits APN more strongly than bestatin, which is its pharmacological inhibitor isolated from Streptomyces olivoreticuli and currently used as an anticancer drug (33,34). Of major interest, endostatin itself was unable to bind to APN and induce these effects; moreover, APN inhibition is dependent on the correct presentation and/or accessibility of the NGR motif (34).…”
Section: Gene Silencing By Specific Sirnas Of Cathepsins L and S Impamentioning
confidence: 99%
“…APN is a zinc-binding type 2 transmembrane ectopeptidase of 150 kDa (Clan MA, family M1; Merops, the peptidase database) that is expressed selectively in vascular endothelial cells, including HUVECs and aortic endothelial cells (32). Previously, it has been shown that a synthetic NGR-containing peptide derived from endostatin (corresponding to the Ser-1451-Thr-1464 moiety and encompassing the sequence of presently identified peptides) binds to and inhibits APN more strongly than bestatin, which is its pharmacological inhibitor isolated from Streptomyces olivoreticuli and currently used as an anticancer drug (33,34). Of major interest, endostatin itself was unable to bind to APN and induce these effects; moreover, APN inhibition is dependent on the correct presentation and/or accessibility of the NGR motif (34).…”
Section: Gene Silencing By Specific Sirnas Of Cathepsins L and S Impamentioning
confidence: 99%
“…In these reactions, at least one intermediate, in which the carbon atom participating in the reaction adopts the sp 3 configuration, is formed. Since phosphonic moiety also has tetrahedral structure and is mimicking this state, phosphonates exhibit inhibitory action towards proteolytic enzymes (Giannousis and Bartlett 1987;Dive et al 2004;Lejczak et al 1989;Mucha et al 2008Mucha et al , 2010Drąg et al 2005). Thus, they might be used as tools for differentiating aminopeptidases from various sources and to determine the structural requirements for their N-terminal fragment binding.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the quite high price and the lack of general methodologies in the design of substrate peptide libraries with non-proteinogenic amino acids, these compounds have not been used on a large scale in proteolytic enzyme studies. More examples of non-proteinogenic amino acid applications can be found in inhibitors or ABPs designed for proteases (Powers et al , 2002 ;Berger et al , 2006 ;Skinner -Adams et al, 2007 ;Mucha et al , 2010 ).…”
Section: Introductionmentioning
confidence: 99%